THE UTILIZATION OF BAMBOO WASTE AS A NEW ALTERNATIVE MATERIAL IN THE AIRCRAFT FUSELAGE INTERIOR PANEL STRUCTURE - Lado Rislya Prakasa (Vortex, 2021)
In the aircraft manufacturing industry, the strength and weight of the material is one of the important considerations in structural design. Composite material is a material composed of two or more forming materials, each of which has different mechanical properties. Aircraft structure in this era are 50 - 80% composed of glass or carbon fiber composite materials as reinforcement. Unfortunately, these fibers when recycled produce harmful CO gas, difficult to degrade naturally and cause itching when in contact with human skin. For this reason, environmentally friendly and strong fibers are needed to replace the role of glass or carbon fibers. Is a bamboo plant, which is abundant in Indonesia which is considered suitable as a substitute material. In this study, a mechanical test and descriptive analysis were carried out on the strength of the composite material with variations in the types of bamboo fibers apus, wulung, tutul and petung. These fibers are arranged with epoxy resin and hardener as a binding material (matrix). And each fiber will be arranged in  0 ° pattern to the matrix. Then each material with a different fiber type will be tested for tensile and bending to obtain the value of stress and strain that occurs at its maximum loading. And the result is the average tensile stress value (Mpa) composite material of apus bamboo is 75.95, wulung bamboo 49.92, petung bamboo 112.73, tutul bamboo 83.85. Then the average bending stress (Mpa) composite material of apus bamboo was 239.073, wulung bamboo 214.236, petung bamboo 249.67, tutul bamboo 272.79. With this result, bamboo fiber composites are considered to be able to replace the role of carbon or glass fibers, as an alternative composite material in some parts of the interior fuselage of aircraft panels. Keyword: Composites material, Matrix, Bamboo Fibers, Carbon and Glass Fibers, Stress and Strain.